Capital Structures In Islamic Capital Markets: Evidences From Bursa Malaysia - Omer Ahmed Salmeen Bin Thabet
The aims of this study are to determine the level of debt of Shariah-compliant firms, the determinants of their capital structure, and the influence of managerial ownership on the relationship between capital structure and its determinants. The study uses cross-sectional and time-series data covering 263 Shariah-compliant firms listed on Bursa Malaysia over the period 2006-201 1. Pooled ordinary least square, fixed effects and random effects methods are used to test the hypotheses of this study. The results show that, first, 79% of Shariah-complaint firms have debt level less than 33%. Second, a significant relationship exists between tangibility, profitability, liquidity, dividends, stock return, risks, zakah, and tax with leverage of Shariah-compliant firms. Finally, in the presence of managerial ownership as moderating variable, only profitability, liquidity, dividends, zakah, tax, and NDTS are found to be a significant with compliant firms' capital structure.